#TITLE_ALTERNATIVE# - (NIM : 23410077) ; Pembimbing Dr. TMA. Ari Samadhi, SUNDANA
An integrated of production schedules with involves purchasing and scheduling policies was developed in this research. The purchasing policy is a deal of material shipment to the suppliers for a specified time interval base on frozen interval of production schedule. The scheduling policy is the replanning interval of the production schedule. The longer of frozen interval means that more certainty there is for material order to suppliers, but the buyer must use more safety stock. Schedule revisions frequently enable the buyer to be more responsive to changes of customer demand, but require more flexibility in the supply chain because the rates of material usage are changing, and schedule revisions rarely foster stability in production schedule, but may be unresponsive for the buyer to changes in customer demands. This research focused on integrating the supply chain through schedule sharing in the stability and responsiveness to the dynamics and uncertainty of the system. The model seeks to find the optimal frozen interval, replanning interval, and safety factor to minimize the expected total cost system that associated with production rate adjustment, safety stock, schedule changes, and shortage. Our models have a better performance than the basic model by 6.59% due to shortage considered to determine safety stock.